Conjugate Free Convection Heat Transfer in Vertical Eccentric Annuli. - Jamal, Ahmad (2002)
Conjugate Laminar free convection heat transfer in vertical eccentric annuli has been numerically investigated. Many practical applications for natural convection in eccentric annuli can be found in electrical, nuclear, solar and thermal fields. In nuclear field, for instance, natural convection cooling of casks containing nuclear waste can exceed thermal guidelines if positioning becomes overly eccentric. Conjugate heat transfer means the transfer of heat from one body to another by means of combined conduction and convection. Heat transfer parameters such as heat flux, Nusselt number and mean bulk temperature have been numerically obtained for different values of eccentricity, wall thickness and conductivity ratio. The effect of eccentricity, conductivity ratio, wall thickness and radius ratio on channel height, required to induce specific flow rate, has also been investigated. Results of the present study are useful in establishing the limits for solid-fluid conductivity ratio, above which, and wall thickness, below which, the conjugate effect can be neglected for practical purposes.